Perceptions on the therapeutic effects of stingless bee honey and its potential value in generating economy among B40 community of Kampung Bukit Kuin, Kuantan - Abd Jalil, Mohd Azri; Ag Damit, Aifa Syazwani; Zakaria, Farahiya Zalikha; Che Hasan, Muhammad Kamil; Md Isa, Muhammad Lokman; Ahmad, Azmir (IOP Publishing, 2022)
Meliponiculture or keeping stingless bee in Malaysia is expanding and has the potential to generate money for the the bottom 40% of income earners (B40). The increased production of stingless bee honey as a complementary medicine as a therapeutic medium for health for a variety of reasons. Thus, this study aimed to explore the experiences and perceptions on the therapeutic effects of stingless bee honey and its potential value in generating economy among the B40 community. Semi-structured interviews were carried out among the B40 community who participated in the Desa Kelulut project of Kampung Bukit Kuin, Kuantan. The data were analysed using thematic analysis. A total of six respondents interviewed in the study out of 20 participants. Four themes emerged, namely, benefit of stingless bee honey; market supply and economy; sustaining the farm; and facilitate income. The participants valued the beneficial properties of the honey toward health and acknowledged the potential of the stingless bee honey to be marketed in Malaysia as well as generating income for the B40 community of Kampung Bukit Kuin, Kuantan.